PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMPN 24 MEDAN - Buana Chandro Sihotang; Elfrianto Elfrianto; Salim Aktar (Universitas Negeri Medan, 2022)
The leadershipp of Schools, Work Motivation, and Job Satisfaction with Teacher Performance of SMPN 24 Medan City. This study aims to determine effect of: (1) leadership headmaster with teacher performance; (2) work motivation with teacher performance; (3) job satisfaction with teacher performance; and (4) leadership headmaster, work motivation, and job satisfaction together with teacher performance. The population of this research is the teacher of SMPN 24 Medan City with the sample is 53 people. The method of research is correlational quantitative research with three independent variables and one dependent variable. Based on the hypothesis testing can be concluded there is a significant relationship between: (1) leadership headmaster with teacher performance of 0.538; (2) work motivation and teacher performance of 0.404; (3) job satisfaction and teacher performance of 0.390; and (4) leadership headmaster, work motivation, and job satisfaction together with teacher performance of 0.666. Overall, the result of the research shows that the improvement of teacher performance can be done through the improvement of leadership headmaster, work motivation, and job satisfaction.